Gambaran Fear of Success pada Wanita Single Pemilik Online Shop di Kalimantan Tengah - Frisca Natasya Tannia; Andhika Alexander Repi (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
It is widespread in society to see the division of labor between women and men based on gender. The daughter helps her mother, and the son helps her father, showing that a woman is more productive in housework. Gender inequality is generated by discriminatory behavior against women caused by this injustice in the division of roles. However, this is different for single women. Until now, they still have problems carrying out responsibilities that must be done, such as running work and taking care of their families. Based on these events, single women experience feelings of fear, known as fear of success. Because of the fear of the negative consequences that may occur if successful, fear becomes a mental barrier to achievement. Every woman must have dreams to achieve, but inadequate circumstances and societal demands make her afraid to succeed. This study uses qualitative methods and is a type of phenomenological research. Theme-driven analysis is used in theory. The information in this study is collected from three single women selected through purposive and snowball sampling. The results of this study show that single women who have experienced fear of success experience the following: fear of themselves, pessimism, doubt about living both roles, pessimism, and difficulty starting new things due to environmental factors.